A Case Study of Students’ Motivation in Learning Human Excretion System - Siagian, Nurjannah Hanum Mahmudah; Rahmawati, Anisa; Eliyawati, Eliyawati; Prima, Eka Cahya (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This research investigates the influence of problem-based learning (PBL) on students' motivation within the context of the excretory system topic in the classroom. Despite introducing various innovative teaching models, student motivation still needs to improve to learn science, prompting the need for practical pedagogical approaches. This study used a case study design, utilizing validated observation sheets and questionnaires as instruments for data collection. With 25 students and one science teacher involved as a sample, qualitative and quantitative data are collected and analyzed through narrative descriptive and transcript analysis and the Rasch model, specifically employing Wright Map and Scalograms value. The findings indicate inadequate implementation of problem-based learning in the teaching excretory system, resulting in persistently low student motivation. Instead of implementing a problem-based learning model, the teacher adopts a teacher-centered approach to deliver the excretory system topic. This leads to minimal active student involvement and engagement in teaching and learning.